LEARNING FROM THE PAST: INNOVATION EVALUATED BY STRATEGIC NICHE MANAGEMENT METHODOLOGY - Emilia van Egmond; de Wilde de Ligny (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2017)
The leading question in this paper concerns the reasons that may stimulate or hamper a wider diffusion of innovative technologies in the construction industry. The Strategic Niche Management (SNM) approach provides an evolutionary framework that is supposed to give a better insight into the reasons why new technologies may be successful or fail even though they promise superior performance compared to incumbent technologies. The SNM approach has been applied in a number of cases of innovative energy and transport technology solutions. The findings will be discussed by thriving on the theoretical backgrounds of the SNM approach and on literature describing the application of the SNM methodology in energy and transport technology cases as well as on the conclusions of the study on the application of it on the wider diffusion of an innovative prefab building system in the Dutch construction industry.